Sto. Rosario Credit Cooperative, Inc. - Buendia, Editha R. (Animo Repository, 1999)
The Sto. Rosario Credit Cooperative, Inc. (SRCCI) is a credit cooperative established in May 1969 by ordinary townfolk from Sabitan, Malolos, Bulacan. Initially, the founders, Engr. Alfredo Aldaba and Mr. Ricardo Santos set out to establish a simple Cooperative Credit Union that would meet the simple financing needs of the people Cooperative Credit Union that would meet the simple financing needs of the people within the community and other neighboring barangays. In September 1969, with a mere capitalization of P 741.00, the Sabitan Cooperative Credit Union, Inc. was formally registered under the Cooperative Administration Office (CAO). In 1975, the Cooperative was registered anew under the Bureau of Cooperative Development*(BCOD). The cooperative was remained the Sto. Rosario Credit Cooperative, Inc. (SRCCI). Since 1987, under Republic Act 6939, all cooperatives in the Philippines, including SRCCI, were placed under the jurisdiction of Cooperative Development Authority (CDA). Throughout its twenty-five (25) years of service to the thirty0one (31) localities included in its area of operations, SRCCI has grown exceptionally well. Its total resources is approximately P173.0 million and it has a total membership base of more than 10, 000 as of 1997. During the same period, it was able to construct three 3-storey buildings, which are used in carrying out the cooperatives daily tasks to serve its members. Services provided by SRCCI to members come in various forms of credit facilities such as regular loans, character loans, commodity loans, special loans, and housing loans. At the end of each year, income from its annual operations is distributed to members after setting aside a portion for the cooperatives reserve funds. SRCCI strives to give the best quality service to its members, not only in terms of fund management, membership solicitation, loan processing, releases and restricting, but also in terms of improving efficiency in its internal operations such as in the area of record-keeping, loans collection and income distribution. In line with this, SRCCI has recently concluded its local area networking computerization program as well as the installation of photo scanners and signature verifiers. The process of setting-up on-line systems to connect its Head Office with its extension offices or branches is also ongoing. And as a means of promoting the welfare of its members, SRCCI continue to launch various projects that would uplift member education, health and expand livelihood activities. In 1993, SRCCI was awarded the Cooperative Hall of Fame* by the provincial government of Bulacan and Most Outstanding Cooperative in the Philippines by the CDA. The award bestowed on the cooperative because of the quality of service it provides to its members. SRCCI has vowed that until there are those individuals who would need assistance cooperatives, it will continue its quest to further improve the way of life of the rural folk in its area of operation. Because of the recent economic turmoil faced by the Asian countries and its adverse effects on the Philippine economy, the financial services industry is indeed experiencing difficulties in its current operations. A major reason for this difficulty is the rising share in the non-performing loans of the banking sector. Apart from banks ( which includes universal, commercial, savings, and rural banks), other institutions in this industry, such as savings and loan associations, investments, pawnshops, lending investors and other non-bank financial institutions are also striving hard to recover from the economic downturn. If such financial services institutions are among those projecting a slight to no-growth returns from operations this year until 1999, then, how should SRCCI execute its operational plans in order to remain competitive? What must it do to be able to meet its targeted increase in membership by 480 members per annum? How will it manage a fast turnover of funds in order to provide fair returns to its members? Thus, this paper documents the current objectives set by SRCCI and analyzes the strategies it has employed in order to attain the goals set in its rural operations.